Cloning and sequencing of a serine proteinase gene from a thermophilic Bacillus species and its expression in Escherichia coli. - Maciver, B (1994)
The gene for a serine proteinase from a thermophilic Bacillus species was identified by PCR amplification, and the complete gene was cloned after identification and isolation of suitably sized restriction fragments from Southern blots by using the PCR product as a probe. Two additional, distinct PCR products, which were shown to have been derived from other serine proteinase genes present in the thermophilic Bacillus species, were also obtained. Sequence analysis showed an open reading frame of 1,206 bp, coding for a polypeptide of 401 amino acids. The polypeptide was determined to be an extracellular serine proteinase with a signal sequence and prosequence. The mature proteinase possessed homology to the subtilisin-like serine proteinases from a number of Bacillus species and had 61% homology to thermitase, a serine proteinase from Thermoactinomyces vulgaris. The gene was expressed in Escherichia coli in the expression vector pJLA602 and as a fusion with the alpha-peptide of the lacZ gene in the cloning vector pGEM5. A recombinant proteinase from the lacZ fusion plasmid was used to determine some characteristics of the enzyme, which showed a pH optimum of 8.5, a temperature optimum of 75 degrees C, and thermostabilities ranging from a half-life of 12.2 min at 90 degrees C to a half-life of 40.3 h at 75 degrees C. The enzyme was bound to a bacitracin column, and this method provided a simple, one-step method for producing the proteinase, purified to near homogeneity.